Transformations of Costa Rican Social Work through Artificial Intelligence - Cascante Vindas, Roberto (2025)
Costa Rican social welfare policy changed with the implementation of the “Sistema Nacional de Registro Único de Beneficiarios del Estado”, a system that not only reproduces the logic of targeting and uses Artificial Intelligence for population selection, but also impacts the work processes of professionals historically embedded in these socio-occupational spaces. Given this scenario, this article analyzes the impact of this system on the role of Social Work within welfare programs since 2017.